Analysis of Treatment and Rehabilitation of Patients with Fractures of the Distal Epimetaphysis of the Tibia Tilyakov Aziz Burievich (Eurasian Medical Research Periodical, 2022)
In recent decades, traumatism has become one of the most pressing problems of modern medicine due to the ever-increasing number of injuries and the high mortality and disability of the injured. In recent years, traumatic deaths have been measured by the number of "non-lived years"; injury-related deaths exceed those caused by cardiovascular diseases, cancers and infectious diseases taken together. This is understandable as the vast majority of deaths from injuries are young people and children.